PERANCANGAN ALAT TETAS TELUR AYAM BERBASIS IOT - Maisura, Mira; Fahrurrazi, Anjas; Firmansyah, Firmansyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This research discusses the design of an Internet of Things (IoT)-based chicken egg incubator aimed at improving efficiency and productivity in the egg hatching process. The device utilizes a DHT22 sensor to measure temperature and humidity inside the incubator and employs an ESP32 microcontroller as the main controller to regulate heaters and fans based on the obtained data. Internet connectivity enables remote monitoring and control through web-based or mobile applications. Test results indicate that the system can maintain temperature and humidity within optimal ranges, specifically between 38ºC to 39ºC for temperature and 72% to 73% for humidity. The implementation of IoT technology in this incubator is expected to enhance egg hatching success rates and reduce operational costs.